2014
DOI: 10.1179/2295333714y.0000000080
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing myopathy as a paraneoplastic syndrome associated with renal cell carcinoma

Abstract: We report a 49-year-old patient with necrotizing myopathy and a right renal mass. After laparoscopic radical nephrectomy, a remission of myopathy was seen. Pathologic evaluation of the nephrectomy specimen revealed a clear cell renal cell carcinoma. Relapse of myopathy 6 months postoperatively coincided with the diagnosis of the appearance of liver metastatic disease. After initiation of treatment with an mTOR-inhibitor, myopathy became less active requiring smaller amounts of corticosteroids with a complete r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…Onconeural antibodies occur only in a small proportion of patients with cancer who develop peripheral neuropathy [7]. Previous case reports of paraneoplastic neuropathies associated with RCC have also described negative antibody screens preceding RCC diagnosis [2, 6, 15, 16, 17, 18–20]. Likewise, our patient was seronegative for common paraneoplastic antibodies including anti-Hu, anti-Ma, and anti-CV2 [21].…”
Section: Discussion and Review Of The Literaturesupporting
confidence: 53%
See 1 more Smart Citation
“…Onconeural antibodies occur only in a small proportion of patients with cancer who develop peripheral neuropathy [7]. Previous case reports of paraneoplastic neuropathies associated with RCC have also described negative antibody screens preceding RCC diagnosis [2, 6, 15, 16, 17, 18–20]. Likewise, our patient was seronegative for common paraneoplastic antibodies including anti-Hu, anti-Ma, and anti-CV2 [21].…”
Section: Discussion and Review Of The Literaturesupporting
confidence: 53%
“…The few neurological syndromes associated with peripheral nervous system manifestations of RCC that have been described are limited mainly to case reports. These syndromes are diverse and include motor neuron disease [3, 4, 5], demyelinating polyneuropathies [2], and myopathies [6, 7]. We present a case of clear-cell RCC associated with unique peripheral nervous system characteristics, including features of a demyelinating polyneuropathy and plexopathy as part of a physiologically complex paraneoplastic syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…These authors hypothesized that the occurrence of squamous cell carcinoma in patients with ADPKD is closely related to the development of polymyositis ( 10 ). Although there have been some reports describing other types of myositis related to RCC ( 8 , 9 ), these are the only reports of polymyositis with RCC as a paraneoplastic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Relapse of the myopathy six months after the operation coincided with a diagnosis of liver metastasis. After the initiation of treatment with an mechanistic target of rapamycin (mTOR) inhibitor, the myopathy became less active, so the authors suggested that it had been closely related to the RCC ( 8 ). Nevins et al reported on a 77-year-old woman who developed severe muscle weakness and was diagnosed with dermatomyositis; a solid mass in the left kidney was also noted.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of ACTH in the postoperative period may be associated with disease recurrence or progression (7). Naert et al (8) reported a case of necrotizing myopathy in a patient with a right renal mass in whom a remission of myopathy was observed after radical nephrectomy. Hypokalemic metabolic alkalosis may occur in patients with Cushing's syndrome (9).…”
Section: Discussionmentioning
confidence: 99%